Penerapan Aplikasi Lakone Dalam Meningkatkan Disiplin Pegawai (Studi Pada Badan Kepegawaian, Pendidikan dan Pelatihan Kota Magelang) - Ayu Widowati Johanes; Vega Fitrika Hendritte; Helianus Rudianto (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2022)
Abstract The Lakone application is an android-based attendance application as an innovation of the Magelang City Personnel, Education and Training Agency which functions as an employee presence tool and a database for employees in Magelang City, as a basis for calculating additional employee income based on the Ministry of Home Affairs Number 900-4700 of 2020 concerning Procedures Approval of the Minister of Home Affairs on Additional Income of State Civil Apparatus Employees in the Local Government Environment. The Covid 19 pandemic requires local governments to innovate from finger print attendance, to Android-based attendance which can be downloaded via the play store. However, after the implementation of attendance through the Lakone application, there are still employees who are late and do not even fill in their attendance in an orderly manner. The purpose of this study is to find out how the application of the Lakone application is related to the level of employee discipline in the Personnel, Education and Training Agency of Magelang City. This research is a qualitative research using a descriptive method with an inductive approach. The technique for collecting data is by using observation, interviews and documentation. The results showed that the implementation of the Lakone application at the Magelang City Personnel, Education and Training Agency had gone well as well as employee discipline had also increased, this can be seen from the results of the monthly attendance recapitulation. However, in its implementation there are still some obstacles, namely servers that often experience errors so that employees cannot do attendance, related to employee discipline there are still employees who cheat by taking advantage of the weaknesses of the Lakone application to carry out activities that benefit themselves. Keywords: Application, Employee Discipline, Lakone Abstrak Aplikasi Lakone adalah aplikasi presensi berbasis android sebagai inovasi Badan Kepegawaian, Pendidikan dan Pelatihan Kota Magelang yang berfungsi sebagai alat presensi pegawai dan tempat database para pegawai di Kota Magelang, sebagai dasar perhitungan tambahan penghasilan pegawai yang berdasarkan Kepmendagri Nomor 900-4700 Tahun 2020 tentang Tata Cara Persetujuan Menteri Dalam Negeri Terhadap Tambahan Penghasilan Pegawai Aparatur Sipil Negara di Lingkungan Pemerintah Daerah. Pandemi Covid 19 mengharuskan pemerintah daerah berinovasi dari absensi finger print, ke absensi berbasis android yang dapat di unduh melalui play store. Namun pasca dilaksanakannya absensi melalui aplikasi Lakone, masih ada pegawai yang terlambat bahkan tidak mengisi presensinya dengan tertib. Tujuan penelitian ini untuk mengetahui bagaimana penerapan aplikasi Lakone terkait tingkat kedisiplinan pegawai di Badan Kepegawaian, Pendidikan dan Pelatihan Kota Magelang. Penelitian ini merupakan penelitian kualitatif menggunakan metode deskriptif dengan pendekatan induktif. Teknik untuk mengumpulkan data yaitu dengan menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan aplikasi Lakone di Badan Kepegawaian, Pendidikan dan Pelatihan Kota Magelang telah berjalan baik begitu juga kedisiplinan pegawai juga telah mengalami peningkatan, hal ini dapat dilihat dari hasil rekapitulasi presensi bulanan. Namun dalam pelaksanaannya masih terdapat beberapa hambatan yaitu server yang sering mengalami error sehingga pegawai tidak bisa melakukan absensi kehadiran, terkait kedisiplinan pegawai masih ada pegawai yang berbuat curang dengan memanfaatkan kelemahan dari aplikasi Lakone untuk melakukan kegiatan yang menguntungkan diri sendiri. Kata Kunci : Penerapan, Disiplin Pegawai, Lakone